2006
DOI: 10.1186/1471-2407-6-43
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge and attitudes of breast self-examination and mammography in a group of women in a rural area in western Turkey

Abstract: Background: Breast cancer appears to be a disease of both the developing and developed worlds. Among Turkish women, breast cancer is the second leading cause of cancer-related deaths. The aims of this cross-sectional study were to determine levels of knowledge about breast cancer and to evaluate health beliefs concerning the model that promotes breast self-examination (BSE) and mammography in a group of women aged 20-64 in a rural area of western Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

35
207
16
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(274 citation statements)
references
References 35 publications
(56 reference statements)
35
207
16
16
Order By: Relevance
“…Similar results were indicated in Iran by Khalili et al Furthermore in line with a significant correlation between with higher academic educational levels and higher rates of BSE practice (Khalili and Shahnazi, 2010). Consistent to our present study, Dundar et al stated no significant variation of education level among BSE performer than non-performer (Dundar et al, 2006). Though Kilic et al found out a linear relationship between increased education levels and BSE performance among participants forming the patient group, this association was not statistically significant (Kilic et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar results were indicated in Iran by Khalili et al Furthermore in line with a significant correlation between with higher academic educational levels and higher rates of BSE practice (Khalili and Shahnazi, 2010). Consistent to our present study, Dundar et al stated no significant variation of education level among BSE performer than non-performer (Dundar et al, 2006). Though Kilic et al found out a linear relationship between increased education levels and BSE performance among participants forming the patient group, this association was not statistically significant (Kilic et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…In this detailed calculation, women only practiced BSE on a monthly basis were found 9.5%, and those performed BSE regularly based on time (Mbanaso et al, 2005). In another study, only 10.2% Turkish women performed BSE regularly on a monthly basis, whereas 29.5% had practiced this method by themselves irregularly (Dundar et al, 2006). It is predicted that the different findings between studies may arouse from the lack of clarity about precise time period on a monthly basis as well as the existence of cultural and demographic features.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the previous studies, it has been stated that BSE barriers, health-related behavior, the perception of the benefits of BSE have been effect on the internal and external barriers which are perceived against understanding the benefits of BSE during the breast cancer surveys. (Dundar et al, 2006;Alpteker et al, 2011). We think that the positive finding obtained in the research study result from the level of knowledge of the students about health and diseases, their comprehension of the impact of the protective forms of behavior on the length and quality of life as well as from their ability to develop a sense of responsibility for their own health.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who perform BSE tend to have more knowledgeable of BC (Dündar et al, 2006). However, many women refrain from using this technique due to a lack of self confidence, shortage of time, and embarrassment associated with manipulation of the breast (Lierman et al, 1994;Stillman 1997).…”
Section: Discussionmentioning
confidence: 99%